2022
DOI: 10.1161/jaha.121.024410
|View full text |Cite
|
Sign up to set email alerts
|

Brugada Syndrome: Different Experimental Models and the Role of Human Cardiomyocytes From Induced Pluripotent Stem Cells

Abstract: Brugada syndrome (BrS) is an inherited and rare cardiac arrhythmogenic disease associated with an increased risk of ventricular fibrillation and sudden cardiac death. Different genes have been linked to BrS. The majority of mutations are located in the SCN5A gene, and the typical abnormal ECG is an elevation of the ST segment in the right precordial leads V1 to V3. The pathophysiological mechanisms of BrS were studied in different models, including animal models, heterologous expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 147 publications
(173 reference statements)
0
18
0
Order By: Relevance
“…It may be caused by primary (idiopathic, tuberculosis, posterior viral or bacterial pericarditis, and connective tissue disease-related) or secondary factors (pericardial injury syndrome or radiation therapy) ( 10 , 11 ). AF was thought to be a part of the natural history of CP; however, it has been reported in only 20–30% of patients with CP ( 12 , 13 ), and more frequently in those with pericardial calcification ( 9 ). Pericardial thickening and/or calcification can be observed in patients with CP using echocardiographic or radiological imaging, although approximately 18% of patients were reported to have a normal pericardium ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It may be caused by primary (idiopathic, tuberculosis, posterior viral or bacterial pericarditis, and connective tissue disease-related) or secondary factors (pericardial injury syndrome or radiation therapy) ( 10 , 11 ). AF was thought to be a part of the natural history of CP; however, it has been reported in only 20–30% of patients with CP ( 12 , 13 ), and more frequently in those with pericardial calcification ( 9 ). Pericardial thickening and/or calcification can be observed in patients with CP using echocardiographic or radiological imaging, although approximately 18% of patients were reported to have a normal pericardium ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…AF was thought to be a part of the natural history of CP; however, it has been reported in only 20–30% of patients with CP ( 12 , 13 ), and more frequently in those with pericardial calcification ( 9 ). Pericardial thickening and/or calcification can be observed in patients with CP using echocardiographic or radiological imaging, although approximately 18% of patients were reported to have a normal pericardium ( 9 ). Annular CP (ACP), an extremely rare form of localized CP, is easily missed or misdiagnosed due to its unusual anatomical form.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 50 gene mutations have been associated with BrS. 2 , 3 But nevertheless, 20%–30% of BrS cases are related to mutations or variants in the SCN5A gene (encoding the ion channel Na v 1.5). Among different variants in the SCN5A gene, the pathogenic role of each variant remains to be experimentally validated.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in animals and several cellular models have suggested a voltage gradient in the early phase of repolarization as a part of the ECG phenotype in BrS. A notched phase 1 of the right ventricular outflow tract myocardial action potential may explain a part of the pathomechanism of J-wave in BrS ( 11 ). This is related to a loss of function sodium channel current ( 12 ).…”
Section: Introductionmentioning
confidence: 99%